Muscle activity in sprinting: a review - Howard, R. M.; Conway, R.; Harrison, A. J. (Sports Biomechanics, 2018)
The use of electromyography (EMG) is widely recognised as a valuable tool for enhancing the understanding of performance drivers and potential injury risk in sprinting. The timings of muscle activations relative to running gait cycle phases and the technology used to obtain muscle activation data during sprinting are of particular interest to scientists and coaches. This review examined the main muscles being analysed by surface EMG (sEMG), their activations and timing, and the technologies used to gather sEMG during sprinting. Electronic databases were searched using `Electromyography` OR `EMG` AND `running` OR `sprinting`. Based on inclusion criteria, 18 articles were selected for review. While sEMG is widely used in biomechanics, relatively few studies have used sEMG in sprinting due to system constraints. The results demonstrated a focus on the leg muscles, with over 70% of the muscles analysed in the upper leg. This is consistent with the use of tethered and data logging EMG systems and many sprints being performed on treadmills. Through the recent advances in wireless EMG technology, an increase in the studies on high velocity movements such as sprinting is expected and this should allow practitioners to perform the analysis in an ecologically valid environment.